Muscarinic Receptor Activity Has Multiple Effects on the Resting Membrane Potentials of CA1 Hippocampal Interneurons - McQuiston, A. Rory (J Neurosci, 1999)
Inhibitory interneurons appear to be an important target for the muscarinic actions of cholinergic inputs to the hippocampus. We investigated the effect of muscarinic receptor activity on the membrane potential (V(m)) and currents of rat hippocampal CA1 interneurons using whole-cell recording from visually identified CA1 interneurons. The predominant response observed was a muscarinic depolarization that was detected in interneurons from all layers of CA1. This depolarization was mediated by at least two mechanisms: a reduction in a potassium current and a mechanism that depended on extracellular sodium. Other interneurons responded to muscarinic agonists with a hyperpolarization or a biphasic response (hyperpolarization followed by depolarization). Hyperpolarizations and biphasic responses were found in all layers of CA1 but more frequently in stratum radiatum and stratum lacunosum moleculare. Muscarinic hyperpolarization was caused by the activation of a barium- and cesium-sensitive inwardly rectifying potassium channel. A small number of interneurons, primarily in or bordering the stratum pyramidale, produced slow membrane potential (0.04 Hz) oscillations. Many interneurons did not respond to muscarinic activity at all; half of these were in the stratum oriens. There was no strong correlation between any changes in V(m) response to muscarine and morphology, as determined by reconstruction of the interneurons. It was not possible to predict the morphology or the layer distribution of an interneuron based on the type of muscarinic membrane potential response it had. This lack of correlation between muscarinic function and morphology implies a greater complexity of interneuron function than has been realized previously.